2018
DOI: 10.1186/s12967-018-1404-z
|View full text |Cite
|
Sign up to set email alerts
|

Double-negative (CD27−IgD−) B cells are expanded in NSCLC and inversely correlate with affinity-matured B cell populations

Abstract: Background:The presence of B cells in early stage non-small cell lung cancer (NSCLC) is associated with longer survival, however, the role these cells play in the generation and maintenance of anti-tumor immunity is unclear. B cells differentiate into a variety of subsets with differing characteristics and functions. To date, there is limited information on the specific B cell subsets found within NSCLC. To better understand the composition of the B cell populations found in NSCLC we have begun characterizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…The facts that [1] DN cells (CD27 − IgD − ) are atypical memory cells, which are reported to be exhausted, anergic, or preplasma cells. The role of DN cells remains unclear, but it has been observed that DN frequency increases during infection (HIV, malaria, Hantavirus), autoimmune disease (SLE, multiple sclerosis), as well as in non-small cell lung cancer (13,(31)(32)(33)(34)(35). In addition, DN cells are reported to express CD11c in HIV, malaria, Hantavirus infection, SLE, and multiple sclerosis (11,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…The facts that [1] DN cells (CD27 − IgD − ) are atypical memory cells, which are reported to be exhausted, anergic, or preplasma cells. The role of DN cells remains unclear, but it has been observed that DN frequency increases during infection (HIV, malaria, Hantavirus), autoimmune disease (SLE, multiple sclerosis), as well as in non-small cell lung cancer (13,(31)(32)(33)(34)(35). In addition, DN cells are reported to express CD11c in HIV, malaria, Hantavirus infection, SLE, and multiple sclerosis (11,36,37).…”
Section: Discussionmentioning
confidence: 99%
“…DN B cells were also found expanded in SLE, HIV and malaria patients, respectively (45)(46)(47), but there is no literature mentioned the relation between DN B cells and T cells till now. Although the origin and function of DN B cells remain unclear, it was suggested that DN B cells may be exhausted memory B cells (48), or precursor memory B cells that have not yet to upregulate CD27 (49), or a product which CD27 fails to upregulate appropriately (50) and the increased DN B cells in SLE patients were considered as precursors of autoantibody producing plasma cells (51). The correlation found in our study implied that DN B cells collaborated with Th2 and Tregs in the immunity against this mycotic infection in human.…”
Section: Discussionmentioning
confidence: 99%
“…The human memory B-cell compartment is more complex than originally thought based on their antigen-experienced phenotype and differential expression of CD27 and immunoglobulin heavy chain isotypes. Though CD27 is a hallmark of memory B cells, CD27 − memory B cells had been identified, namely CD27 − IgG + and CD27 − IgA + classswitched B cells (Fecteau et al, 2006;Wei et al, 2007;Berkowska et al, 2011;Centuori et al, 2018).…”
Section: Memory B Cell Subsetsmentioning
confidence: 99%
“…The CD27 − memory B cell subset has undergone class switching, though they do not gain the expression of CD27. Little is known about the function of these cells in immunity (Centuori et al, 2018). It is therefore tempting to postulate that CD27 − memory cells develop outside the GC in extrafollicular reactions.…”
Section: Memory B Cell Subsetsmentioning
confidence: 99%